Eating disorders in secondary school students - Torres-Cruz, Edward (2021)
It is undoubtedly of interest to education and health professionals to know the characteristics of eating disorders in secondary school students, who are in a stage of behavioral training. Eating behavior disorders were analyzed in secondary school students of the Little Rome of America in Juli, Puno, Peru. The study subjects were selected from the most representative educational institution of the city, in order to evaluate and lay the foundations for the diagnosis of eating disorders, using the Eating Attitudes Test - 40 as an instrument, in which 58 students from second to fifth grade between males and females participated, with an average age (X=15. 06, SD = 1.13), a risk-disorder of 48.3% has been confirmed, likewise, a prevalence of 37% in females and 10% in males was evidenced, which confirms the presence of eating disorders and implies facing it from the basic training of students to establish a behavioral prevention.